(untitled) (Global Journal of Science Frontier Research, 2011)
Vibrational dynamics of the poly 3,3-dimethyloxetane (form III) is being reported using Higg’s method and Urey Bradley force field. Characteristic features of dispersion curves such as repulsion, crossing and bunching are reported. A comparitive study of the two polymorphic forms (form II and III) is presented and possible regions for variation in heat capacity are discussed.